The effects of meloxicam, lornoxicam, ketoprofen, and dexketoprofen on human cervical, colorectal, and mammary carcinoma cell lines - Lyubomir Marinov; Ani Georgieva; Reneta Toshkova; Ivanka Kostadinova; Iliya Mangarov; Tanya Toshkova-Yotova; Irina Nikolova (Pensoft Publishers, 2024)
Targeting the inflammation-related molecules with nonsteroidal anti-inflammatory drugs (NSAIDs) represents a promising approach for cancer prevention/therapy. We evaluated the in vitro anticancer effects of meloxicam, lornoxicam, ketoprofen, and dexketoprofen on the proliferation, migration, and apoptosis of human cervical, colorectal, and mammary carcinoma cells. The antiproliferative activity and cytotoxicity of tested NSAIDs on HeLa, HT-29, and MCF-7 cell lines were assessed by the MTT test. The apoptosis-inducing potential was analyzed by fluorescent staining with acridine orange/ethidium bromide and DAPI. Migration activity was assessed by a wound-healing scratch assay. The tested NSAIDs reduced the viability of the used tumor cell lines. The cytomorphological analysis revealed reduced cell density and mitotic activity and the presence of cells with morphological features of early and late apoptosis. Significant inhibition of the migration capacity was established as well. In conclusion, NSAIDs could be candidates for the development of new pharmacological strategies for the treatment and prevention of cancer.